2019
DOI: 10.1177/0361198119847980
|View full text |Cite
|
Sign up to set email alerts
|

Freeway Truck Traffic Safety in Wyoming: Crash Characteristics and Prediction Models

Abstract: The State of Wyoming experiences a high percentage of truck traffic along all its highways, especially Interstate 80 (I-80). The increased interactions between trucks and other vehicles have raised many operational and safety concerns. This paper presents a safety analysis and a development of safety performance functions (SPFs) along I-80, with a focus on truck crashes. Nine years of historical crash data in Wyoming (2008–2016) were used to observe the involvement of light, medium, and heavy trucks in crashes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Wen et al [56] found that the curvature was positively associated with the property damage accidents only. Haq et al [31] found a decreasing impact of horizontal curve radius on the truck related accidents. Studies also show that setting more gradual horizontal curves can reduce the number of accidents [46].…”
Section: Geometric Design Elementsmentioning
confidence: 96%
See 4 more Smart Citations
“…Wen et al [56] found that the curvature was positively associated with the property damage accidents only. Haq et al [31] found a decreasing impact of horizontal curve radius on the truck related accidents. Studies also show that setting more gradual horizontal curves can reduce the number of accidents [46].…”
Section: Geometric Design Elementsmentioning
confidence: 96%
“…Traffic composition was used as an important independent variable by various researchers to identify the safety effects on expressway. Some researchers [20,24,31] found that higher percentage of trucks in traffic volume on expressway causes more number of accidents, and this could be attributed to the difference of speed between light vehicles and heavy vehicles. However, other researchers [11,47,57] found that high fraction of trucks and trailers in traffic volume result in decreasing accident risk.…”
Section: Traffic Conditionsmentioning
confidence: 99%
See 3 more Smart Citations